2015
DOI: 10.1103/physrevb.91.014308
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a thermodynamic potential for the water ices VII and X

Abstract: We employ a combination of density functional theory (DFT), molecular dynamics (MD), and a variety of advanced postprocessing methods to construct an analytic thermodynamic potential (free energy) for ices VII and X. In particular, the temperature-dependent part of the free energy function is constructed using entropy data obtained via the spectrum of vibrational modes from the MD simulations. Conceptional challenges due to the partial absence of stable zero-temperature states and proton disorder are overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 83 publications
(131 reference statements)
11
58
0
Order By: Relevance
“…Quantum effects of the nuclear motion cannot be neglected when calculating the thermodynamic properties of SIW. Equation (3) allows us to include such effects at the same level as was recently done for the ices VII and X [30] or earlier calculations for fluid water [44,67]. In the case of fluid ammonia, it was shown that the method can capture effects of thermal dissociation that lead to an increased decay of the nuclear quantum effects due to the loss of intramolecular modes of vibration [61].…”
Section: B Nuclear Quantum Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum effects of the nuclear motion cannot be neglected when calculating the thermodynamic properties of SIW. Equation (3) allows us to include such effects at the same level as was recently done for the ices VII and X [30] or earlier calculations for fluid water [44,67]. In the case of fluid ammonia, it was shown that the method can capture effects of thermal dissociation that lead to an increased decay of the nuclear quantum effects due to the loss of intramolecular modes of vibration [61].…”
Section: B Nuclear Quantum Correctionmentioning
confidence: 99%
“…Having obtained the complete thermodynamic information of the SIW phases, we then investigate the location of transitions between them. The boundary to the dense ices VII and X, for which a corresponding thermodynamic potential is also available [30], is calculated as well. It is in good agreement with that observed directly in the MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Lower: thermal conductivity of ice VII at T=300 K in comparison with experiments[39,40]. Pressures for the DFT-MD+GKFF points were calculated with an equation of state[41].…”
mentioning
confidence: 99%
“…This transition sequence-orientational disorder (ice VII) to dynamical disorder (ice VII 0 ) to ionic ice (ice X) -was studied at ambient temperature, but few studies mention it at high temperature [21,22]. With increasing temperatures, the mobility of the protons is enhanced such that H 2 O ice reaches a superionic state [23] while the sublattice of oxygen atoms remains fixed.…”
mentioning
confidence: 99%